Rural-Urban Dynamics in the East African Mountains - Racaud, Sylvain; Nakileza, Bob R.; Bart, François; Charlery de la Masselière, Bernard (Africae Studies, 2016)
This edited volume brings to light how much the development of the mountains of East Africa relates to their surrounding fast-growing towns and cities. The contributors, most of them geographers from both East Africa and France, explore three cases: Mount Kenya (Kenya), Mount Elgon (on its Ugandan side), and the Uporoto Mountains (Tanzania). They adopt a comparative perspective with earlier research and other East African mountains, such as Mount Kilimanjaro. The 12 chapters focus on one major recent upheaval: the growing urbanization that shapes new mountain systems. This phenomenon gives rise to the following questions: What are the links between rural and urban changes in such contexts? What are their impacts on livelihoods and development? This book, covering social and environmental issues relating to rural-urban exchanges and transformations, is the first of its kind for African mountains.